Respostas
respondido por:
5
x2 - 3x = 28
x2 - 3x - 28 = 0
Δ = b² - 4.a.c
Δ = -32 - 4 . 1 . -28
Δ = 9 - 4. 1 . -28
Δ = 121
Aplicando Bhaskara:
x = (-b +- √Δ)/2a
x' = -(-3 + √121)/2.1
x' = 14 / 2
x' = 7
x'' = -(-3 - √121)/2.1
x'' = -8 / 2
x'' = -4
Logo, x pode ser 7 ou -4.
respondido por:
1
Olá, bom dia ☺
Resolução:
x² - 3x = 28
x² - 3x - 28 = 0
-----------------------------
(x - 7).(x + 4) = 0
Primeira raiz....
x - 7 = 0
x' = 7
Segunda raiz...
x + 4 =0
x''= -4
S={7,-4}
Bons estudos :)
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás